Wip1 inhibitor CCT007093 alleviates immune exhaustion of lymphocytes via p65 NF-κB and YY1 in chronic hepatitis B virus infection in mice - You, Yu-Syuan; Chang, Wan-Ting; Hsu, Chia-Lang; Wang, Hui-Ying; Lu, Yan-Fong; Kim, InKyeom; Tzeng, Shiang-Jong (Frontiers in Immunology, 2025)
IntroductionProlonged viral infections often lead to lymphocyte exhaustion, marked by heightened inhibitory receptor expression like PD-1, compromising host defense mechanisms. The unexplored potential of chemical checkpoint inhibitors in rejuvenating immune responses prompted our investigation.MethodsWe focused on CCT007093, a Wip1 inhibitor, screened for its distinctive capacity to simultaneously decrease PD-1 and FcγRIIB expression in B cells.ResultsIn this study, we harnessed a murine model of immune exhaustion induced by chronic hepatitis B virus (HBV) infection using hydrodynamic injection. Treatment with CCT007093 resulted in decreased levels of PD-1 expression, resulting in reduced percentages of PD-1+/hi CD4+ and CD8+ T cells in circulation, spleen, and liver. The expression levels of PD-1 and FcγRIIB, along with the percentages of PD-1+/hi and FcγRIIB+/hi CD19+ B cells in these tissues, were similarly diminished. Moreover, intrahepatic lymphocytes treated with CCT007093 displayed heightened responsiveness to ex vivo activation. Consequently, mice treated with CCT007093 exhibited significantly reduced serum HBsAg levels compared to vehicle-treated mice. Our detailed analyses, spanning promoter and transcriptome evaluations, uncovered p65 NF-κB as the primary activator of T cells and B cells, while Ying Yang 1 (YY1) emerged as the key regulator, orchestrating the down-regulation of PD-1 and FcγRIIB gene transcription in response to CCT007093.DiscussionOur study highlights the prowess of chemical checkpoint inhibitors, exemplified by CCT007093, in alleviating immune exhaustion in HBV-infected mice, particularly by enhancing adaptive immunity.